Difficulties Faced by Translators in Translating English Texts into Makassarese - Tahir, Tahir; Hasan, Rahmat (English Literature Studi Program Universitas Islam Makassar, 2024)
This research aims to investigate the difficulties faced by translators in translating English text into Makassarese as well as to identify the most frequent difficulties. A qualitative research method was employed, involving ten university students from the fourth and sixth semesters at Universitas Muhammadiyah Makassar. These students translated texts extracted from a handbook used at Junior High School 1 Mamuju. The research revealed that 40% of the students identified issues at the word level as the most significant challenge, while 30% reported difficulties with syntactic translation, and another 30% encountered problems with semantic translation. In response to these difficulties, the majority of students preferred employing either free or literal translation methods, as these approaches facilitated a clearer understanding of the English text and their translation into Makassarese. Furthermore, this research highlights the necessity of developing effective strategies to address various levels of translation difficulties, with the aim of enhancing the accuracy and efficiency of translating English text into Makassarese.